Testing the local mate competition rule in a quasi-gregarious parasitoid with facultative superparasitism. (6th February 2023) - Liu, Peng-Cheng; Wang, Zi-Yin; Qi, Mei; Hu, Hao-Yuan
Abstract: As an important domain of evolutionary ecology, sex allocation theory well explains the evolution of investment into female versus male offspring. Local mate competition (LMC) is a good predictor of sex allocation, where the optimal sex ratio becomes less female-biased and asymptotically approaches 0.5 as the number of foundresses increases. Parasitoid wasps, with haplodiploid sex determination, offer excellent opportunities to test how organisms manipulate their offspring sex ratio in response to environmental variation, and many species have been proved to allocate sex according to predictions under LMC. When hosts are spatially clustered, as in gregarious species, the mating systems of quasi-gregarious parasitoids meet the essential assumptions (female mating before dispersal) of LMC. However, inconsistent with predictions, in the quasi-gregarious species Anastatus disparis (Hymenoptera: Eupelmidae), a strongly female-biased eclosion sex ratio (0.156 ± 0.018 to 0.185 ± 0.016) was observed as the number of females laying eggs in a patch increased. Superparasitism, in which 44.7% of parasitized hosts contained more than one egg but only one adult emerged from each host, was common in A. disparis . However, the egg sex ratio was determined by microsatellites and likely fit the predictions of LMC theory. Male-biased offspring mortality arising from superparasitism during development likely contributes to the shift from the primary sex ratio predicted under LMC to the observed female-biased eclosion sex ratio. Inconsistent with results in gregarious parasitoids, the role of superparasitism in driving sex ratio shifts in quasi-gregarious parasitoids should be incorporated into LMC-based predictions of sex ratios. Abstract : In a partly social parasitoid wasps, females produce more male-biased egg sex ratios as the number of egg-laying females increases, in line with the predictions of local mate competition (LMC) theory. However, we found a strong female bias in eggs that hatched. Superparasitism during development likely contributes to the shift from the primary sex ratio predicted under LMC theory to the observed female-biased hatching sex ratio.